The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/1519-6984.265583
|View full text |Cite
|
Sign up to set email alerts
|

First record of Cosmocerca podicipinus (Nematoda: Cosmocercidae) parasitizing Leptodeira annulata (Serpentes: Dipsadidae) in northeastern Brazil

Abstract: Although L. annulata is parasitized with several parasite species, there is no report of infection of a snake host with species of the genus Cosmocerca. Here we report the occurrence of C. podicipinus in one adult female of L. annulata (snout-vent length 611 mm), collected on May 26 th , 2018, in the Sete Cidades National Park (4°06′01" S, 41°42'27" W; datum WGS 84; 191 m a.s.l.), in the municipality of Piripiri, state of Piauí, Brazil. The voucher snake was deposited in the Herpetological Collection of the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Leptodeira annulata (Linnaeus), the cat-eyed snake, is widely distributed throughout Brazil and found in all Brazilian biomes ( Costa and Bérnils, 2018 ). Studies regarding this species have been focusing on foraging, diet, and reproduction, with a small number of studies addressing its helminth fauna ( Sprent, 1988 ; Mesquita et al, 2013 ; Silva-Neta et al, 2015 ; Carvalho et al, 2018 ; Ferreira-Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptodeira annulata (Linnaeus), the cat-eyed snake, is widely distributed throughout Brazil and found in all Brazilian biomes ( Costa and Bérnils, 2018 ). Studies regarding this species have been focusing on foraging, diet, and reproduction, with a small number of studies addressing its helminth fauna ( Sprent, 1988 ; Mesquita et al, 2013 ; Silva-Neta et al, 2015 ; Carvalho et al, 2018 ; Ferreira-Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nematodes parasites of Leptodeira annulata are poorly known; however, some studies have already reported nematodes parasitizing this host, such as Hexametra boddaertii Baird 1860, Ophidascaris trichuriformis Vaz 1935, Raillietnema spectans Gomes 1964, Oswaldocruzia sp., Oxyascaris sp., Physaloptera sp., and Cosmocerca podicipinus Baker and Vaucher (1985) ; Sprent (1988) ; Carvalho et al (2018) ; Ferreira-Silva et al (2022) .…”
Section: Introductionmentioning
confidence: 99%